High accuracy measurement of gravitational wave back-reaction in the OJ287 black hole binary. Issue Volume 13:Issue S338(2017) (29th January 2019) - Valtonen, Mauri J.; Dey, L.; Hudec, R.; Zola, S.; Gopakumar, A.; Mikkola, S.; Ciprini, S.; Matsumoto, K.; Sadakane, K.; Kidger, M.; Gazeas, K.; Nilsson, K.; et al.
Abstract: Blazar OJ287 exhibits large thermal flares at least twice every 12 years. The times of these flares have been predicted successfully using the model of a quasi-Keplerian eccentric black hole binary where the secondary impacts the accretion disk of the primary, creating the thermal flares. New measurements of the historical light curve have been combined with the observations of the 2015 November/December flare to identify the impact record since year 1886, and to constrain the orbit of the binary. The orbital solution shows that the binary period, now 12.062 years, is decreasing at the rate of 36 days per century. This corresponds to an energy loss to gravitational waves that is 6.5 ± 4 % less than the rate predicted by the standard quadrupolar gravitational wave (GW) emission. We show that the difference is due to higher order gravitational radiation reaction terms that include the dominant order tail contributions.